THE INFLUENCE OF WORK-LIFE BALANCE ON THE MENTAL HEALTH OF MILLENNIAL GENERATION WORKERS IN YOGYAKARTA SPECIAL REGION - Dina Tika Riyani; Sri Handayani (Antis Publisher, 2024)
The research had the objective to analyze the effect of work life balance on the mental health of millennial generation employees of the Yogyakarta Special Region. This research includes causal associative research with quantitative approach. The sampling method was simple random sampling with the Slovin formula at a critical value of 10% and get results from 131 respondents. Primary data was conducted using questionnaire trough google forms. The statistical tests used are validity test, reliability test, normality test, heteroscedasticity test, linearity test, simple linear regression analysis, t test and analysis of the coefficient of determination with the SPSS Statistic 26.0 Program. The results of data analysis indicated that a positive and significant influence on work life balance to mental health with a correlation value of 0.667. Effective contribution from work life balance to predict mental health by 41.8% and the remaining 58.2% influenced by other factors not examined in this study. Thus, it can be concluded that the hypothesis in this research is accepted.